2008
DOI: 10.1099/vir.0.2008/003749-0
|View full text |Cite
|
Sign up to set email alerts
|

RNase-dependent inhibition of extracellular, but not intracellular, dsRNA-induced interferon synthesis by Erns of pestiviruses

Abstract: Recombinant pestivirus envelope glycoprotein E rns has been shown to interfere with dsRNAinduced interferon (IFN-a/b) synthesis. This study demonstrated that authentic, enzymically active E rns produced in mammalian cells prevented a dsRNA-induced IFN response when present in the supernatant of bovine cells. Strikingly, IFN synthesis of cells expressing E rns was eliminated after extracellular addition, but not transfection, of dsRNA. Importantly, the same applied to cells infected with bovine viral diarrhea v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 28 publications
1
87
0
2
Order By: Relevance
“…Both in vitro analyses and experiments with BVDV-infected fetuses showed that E rns is involved in pestiviral interference with the type I IFN response to virus infection (21,31,33). It was therefore interesting to investigate whether differences in the type I IFN levels could be detected in the blood of infected pigs from groups 1, 2, and 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both in vitro analyses and experiments with BVDV-infected fetuses showed that E rns is involved in pestiviral interference with the type I IFN response to virus infection (21,31,33). It was therefore interesting to investigate whether differences in the type I IFN levels could be detected in the blood of infected pigs from groups 1, 2, and 3.…”
Section: Resultsmentioning
confidence: 99%
“…It has been put forward that secreted E rns could be responsible for blocking an IFN response to extracellular dsRNA. Evidence for this hypothesis was found in in vitro experiments, and it was shown that the RNase activity of E rns is essential for this function (21,31). However, the putative origin of this so-far hypothetical extracellular RNA is obscure, and it might be that E rns (also) serves other functions.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The nonstructural protein N pro targets the transcription factor IRF3 for proteasomal degradation (5), thus antagonizing interferon induction, e.g., by double-stranded RNA (dsRNA), in virus-infected cells (6,7). E rns harbors an RNase active domain belonging to the T2 RNase superfamily (8), and this enzymatic activity is essential for its ability to block the induction of IFN-␣/␤ (9)(10)(11). Together with viral glycoproteins E1 and E2, E rns forms the envelope of the virus, but a significant portion of the E rns protein is also secreted into the extracellular space (8).…”
mentioning
confidence: 99%
“…As differences in viral replication did not explain differences in IFN-␣/␤ production, we next assessed the potential effects of both BVDVncp strains on interferon response factors (IRFs). BVDVncp is known to inhibit IFN-␣/␤ production through viral proteins N pro (2,3,10,14) and E rns (16,18,19), which block IFN-␣/␤ production by targeting IRF-3 for degradation by polyubiquitination (7,14) or by degrading viral RNA (19). Translocation of IRF-3 occurs during infection but not binding to DNA (2).…”
mentioning
confidence: 99%